A Collaborative Approach for the Development of Networked Learning Environments Using the ADDURI Framework - Valkanos, Nikolaos (Proceedings of the International Conference on Networked Learning, 2008)
Advances in Information and Communication Technologies (ICTs) have made it possible to reach a large number of distance learners beyond the correspondence tuition models traditionally used in open and distance learning. Designers and developers are increasingly working with Virtual Learning Environments (VLEs) for distance teaching and learning. However, designing and implementing such learning systems remains a challenge due to the many interrelated components, factors, choices and many possible approaches. In this paper we present the ADDURI (Analyse, Design, Develop, Use, Review, Improve) resource based learning and teaching framework. We analyse the key cross-disciplinary activities that influence the inter-relationships of the groups in order to provide a systematic methodology for the development of Collaborative Networked Learning Environments, and provide guidelines for the adoption and use of the framework. The design and realisation of an effective e-learning system involves multidisciplinary knowledge and collaborative efforts of a spectrum of scientists, e-learners and educators. E-learning itself is a combination of many other existing fields and as such, whatever happens in technology, learning theory, web design, network analysis, etc. impacts and shapes e-learning. Effective instruction in any mode is a result of careful planning that follows a transparent process from the project idea to evaluation and review. Thus, in developing an e-learning system there is a need to face the matter in a systemic (holistic) approach. The ADDURI framework was proposed aiming to integrate know how from information systems development and instructional design. The goal was to create a general e-learning framework for offering technology-based learning independent of teaching methodologies. The framework is flexible in order to allow different teaching and learning techniques, and thinking tools to be used for delivering a course. The ADDURI framework consists of six phases, as its acronym indicates, namely, Analyse, Design, Develop, Use, Review and Improve. It is largely based on the software development lifecycle followed by several IS development methods. The framework itself needs to be adapted to the knowledge needs, technological infrastructure, culture or any other predefined target of specific organisations. The ADDURI improvement cycle operates simultaneously at two levels. Each phase is itself a cyclic process with sub-phases and deliverables feeding into the next phase. The development of technology-based learning resources follows a self-similar lifecycle, providing a continuous improvement loop overall and similarly. The notion of collaboration spans a very broad spectrum of participants, applications, devices and platforms, from simply sharing information with another person, department or organisation to unifying communication processes and content and establishing forms for accessing resources and building content. The purpose of collaboration is to combine expertise and resources in order to meet the needs of all learners. What is expected from collaboration is supportive interactive group learning, shared understanding, social construction of knowledge and acquisition of competences. During the development of a networked learning course there are certain groups of people that collaborate amongst “clusters”. There is also an internal collaboration amongst the elements within each group. The four “clusters” or groups are: 1 Field Experts (People knowing the learning domain, such as teachers/instructors), 2 ICT Experts (ICT staff, methods and tools), 3 Learners (students with different learning preferences and levels of previous knowledge and experience), 4 Resources (Internal learning material developed by instructors and students and external learning material in on-line libraries, web-pages, web 2.0, etc.). The eLearning initiative of the European Commission seeks to mobilise the educational and cultural communities, as well as the economic and social players in Europe, in order to speed up changes in the education and training systems for Europe’s move to a knowledge-based society. Globalisation, new technologies and demographic developments constitute an enormous challenge; one of the answers to this problem is the access to lifelong learning.